Comparative Analysis of anti-Shine- Dalgarno Function in Flavobacterium johnsoniae and Escherichia coli - McNutt, Zakkary A.; Gandhi, Mai D.; Shatoff, Elan A.; Roy, Bappaditya; Devaraj, Aishwarya; Bundschuh, Ralf; Fredrick, Kurt (Frontiers in Molecular Biosciences, 2021)
The anti-Shine-Dalgarno (ASD) sequence of 16S rRNA is highly conserved across Bacteria, and yet usage of Shine-Dalgarno (SD) sequences in mRNA varies dramatically, depending on the lineage. Here, we compared the effects of ASD mutagenesis in Escherichia coli, a Gammaproteobacteria which commonly employs SD sequences, and Flavobacterium johnsoniae, a Bacteroidia which rarely does. In E. coli, 30S subunits carrying any single substitution at positions 1535-1539 confer dominant negative phenotypes, whereas subunits with mutations at positions 1540-1542 are sufficient to support cell growth. These data suggest that CCUCC (1535-1539) represents the functional core of the element in E. coli. In F. johnsoniae, deletion of three ribosomal RNA (rrn) operons slowed growth substantially, a phenotype largely rescued by a plasmid-borne copy of the rrn operon. Using this complementation system, we found that subunits with single mutations at positions 1535-1537 are as active as control subunits, in sharp contrast to the E. coli results. Moreover, subunits with quadruple substitution or complete replacement of the ASD retain substantial, albeit reduced, activity. Sedimentation analysis revealed that these mutant subunits are overrepresented in the subunit fractions and underrepresented in polysome fractions, suggesting some defect in 30S biogenesis and/or translation initiation. Nonetheless, our collective data indicate that the ASD plays a much smaller role in F. johnsoniae than in E. coli, consistent with SD usage in the two organisms.